(untitled) (World Science, 2022)
Possibilities and prospects of correcting women’s health disorders associated with hypoestrogenic conditions of various etiologies or hormonal imbalances are considered. The causes of estrogen deficiency and features of complaints in women of different ages with an emphasis on peri- and menopause are systematized. An alternative to menopausal hormone therapy (MHT) with the use of phytovitamin preparations is considered. The relationship of hormonal metabolism with vitamin and mineral status, feasibility and benefits of complex phyto-, vitamin- and mineral preparations is shown. The therapeutic efficacy of medicinal plants that are part of the complex phytopreparation "Forevia Maxi" ("Organosyn LTD") in accordance with the symptoms of premenstrual syndrome (PMS): vasomotor (shortness of breath, hot flushes, night sweats, blood pressure fluctuations), genitals and atrophy of the vagina, itching, burning, cystalgia, urinary incontinence, dyspareunia) complications, memory and cognitive impairment, decreased sexuality, libido, sleep disorders, mood swings, anxiety, depression, aggravating psycho-emotional state, osteoporotic changes. Data from clinical trials of phytoextracts are shown, which demonstrate that the effect of the components of Forevia Maxi significantly exceeds the effect of placebo, and sometimes not less than with the use of MHT. The obvious benefits of this tool and as an adjunct to the basic therapy of PMS and hypoestrogenic conditions, characterized by ease of use, good safety profile, allows you to individualize the approach to patients, which is important in cases of medical contraindications for hormone therapy. Forevia Maxi is also the most appropriate for use with MHT, as an additional component of the correction of hypothalamic-pituitary disorders and saturation of the body with essential minerals and vitamins.